Extração e caracterização físico-química do amido nos cormos de Trimezia juncifolia (KLATT) Benth & Hook - Cruz, Viviane Ovidio de Almeida (2019)
The members of Iridaceae family have the storage of carbohydrates in underground organs as main characteristic. Some Iridaceae species might store more than one type of carbohydrate, being starch the main reserve compound. Trimezia juncifolia belongs to the Iridaceae family and has a corm as an underground reserve organ and has fibrosis cataphylls, which presents a large amount of starch. This starch reserve is used to provide energy during the onset of vegetative growth and to maintain metabolism during periods of stress, such as the seasonal drought, when the plant is under the phenological stage of dormancy, interrupting its growth and reducing its metabolism. Starch is a semi-crystalline polysaccharide composed of two types of polymers: amylose and amylopectin. The starch is stored as granules and may present differences in morphology, crystalline structure, amylose and amylopectin ratio and chain size, depending on the botanical origin. In this sense, the objective of this work was to extract and characterize the starch from corms of T. juncifolia collected in the dry and wet season. Results evidenced a yield of starch extraction in the range of 57.2% in the wet season and 69.2% in the dry season. The starch granules presented a bimodal size distribution. The size of starch extracted in the dry season was higher (3.69-33.75 μm) than extracted in the wet season (2.78-14.4 μm) and both presented shape similar to wheat starch. The content of amylose was 44 % and 41 % for starch from corms collected in dry season and wet season, respectively. The birefringence of starch granules was higher in wet season. The degree of polymerization of amylopectin analyzed through chromatography showed a slight difference between starch from wet (DP 81) and dry (DP 80) season. Amylose branches showed higher difference in the degree of polymerization between wet (DP 51) and dry (DP 41) season. X-ray analysis revealed differences in starch stored in the corms. Starch from dry season presented similarity with type-A polymorph more compact whereas a C-type polymorph a mixture of type-A and type-B was observed in the wet season. The crystallinity values were 27% and 25.9% for wet and dry season starches, respectively. The endothermic transition temperature were: wet season To= 39.7 ºC, Tp= 84.1ºC, Tc= 157.4 ºC and ΔT = 117.7 ºC; dry season: To= 27.6 ºC, Tp= 73 ºC, Tc= 116.6 ºC and ΔT = 89 ºC. Furthermore, the enthalpy changes (wet season: ΔH = 84.9 J g−1 / dry season: ΔH = 54.9kJ g−1) were accessed by DCS analysis. In conclusion, the results of this study indicate that the water availability in the environment results in biochemical changes in the characteristics of the starch stored in the cataphylls from T. juncifolia.